PENGARUH BAURAN PEMASARAN RITEL TERHADAP KEPUASAN PELANGGAN MINIMARKET INDOMARET PERUMAHAN SAWOJAJAR I MALANG - Agung W, Rachmat (Department of Management, 2016)
The performance of a retail company is inseparable from the performance attributes of the marketing mix used by retail companies. The marketing mix is generally called on a retail company with ritailing mix. Attribute of ritailing mix consists of product, price, place, promotion, presentation and personnel (6 p). The ritailing mix is also believed to affect the satisfaction of the company's retail customers. So in this study is intended to determine the influence of ritailing mix consisting of attributes of the product, price, place, promotion, presentation and personnel against modern retail customer satisfaction. This research is the research of causality, which aims to explain the influence of the change of variable values in a common variation to the changing value of the variation in one or more other variables. Methods of analysis used in the study are using the multiple linear regression method with sampling purposive sampling method. Data from the questionnaire distributed to 100 customers a minimart Indomaret Sawojajar Housing I Malang became the primary data source. Based on the results of data analysis conducted, it was concluded that a variable price, promotion and presentation which is an attribute of ritailing mix affect significantly to customer satisfaction. While the variable product, place, and influential significance level personnel with a different. This research also concluded that an attribute of ritailing mix are jointly contributing significantly to customer satisfaction with the value of significance 0,000, and has the value of the influence of 58.6% of customer satisfaction and the rest is influenced by other variables which are not examined in this study.